Investigating older persons and NGOs flood preparedness to reduce vulnerabilities associated with ageing: a case study - Hussain, Rizal M; Syed Abd Rashid, Sharifah Norazizan; Sabri, Bukryman; Bagat, Mohamad Fazdillah (THEIJSSHI, 2018)
The impact of natural disasters on the older population is unlikely to diminish in the years to come due to the increasing number of older persons in Malaysia. Recent trends with respect to management of natural disasters have highlighted the role of NGOs in all phases of disaster management namely preparedness, response, recovery and mitigation. Research showed a notable difference emerged between the perceptions of the older persons, and those of the respondents from aid agencies (government and NGO) dealing with emergencies. In this research paper, information on specific needs and problems faced by older persons during the 2014 flood as well as the NGOs perceptions towards them were identified. It also studied the impact of flood disaster on older persons. Their preparedness to face emergencies and the suitability of the relief programs organized by NGOs were investigated. A mix method approach was adobted in this research which include qualitative (Focus Group Discussion) and quantitative (face-to-face interview) survey. Data was analyzed using Statistical Package for Social Science (SPSS). Based on findings from the FGDs conducted, there was no Standard Operating Procedure on flood relief for the older persons adopted by the NGOs. There is a clear need for SOPs to ensure proper guidelines and procedures in meeting the special needs of the older persons in times of disasters